Ruqyah Complementary Therapy in Cluster Headache Patient in Indonesia - Indri Seta Septadina; Nita Parisa (HM Publisher, 2021)
This case report presents a Malay Muslim man with a severe cluster headache. The patient responded only to morphine treatment, but his condition continued to worsen. He uses the complementary therapy of ruqyah, which is based on a verse from the Qur'an, after seeking advice from a local ulama (Islamic cleric). His condition improved significantly, and he underwent preventive ruqyah therapy on television. Since switching to ruqyah, he is no longer on morphine treatment, and the level and duration of her pain is significantly reduced. Ruqyah therapy is famous for treating jinn possession but has also been found to have a therapeutic effect on organic health problems. The case illustrates that supplementing modern medicine with ruqyah can bring many benefits, especially in the Muslim community.